Ceramic composite diaphragm and battery
By setting a ceramic coating on the base film of the ceramic composite separator and controlling the characteristic parameter P range of polyvinyl alcohol and sodium carboxymethylcellulose, the problem of increased breathability and insufficient heat resistance at high temperatures is solved, low heat shrinkage and low breathability increase are achieved, and the circulation performance and safety of the battery are improved.
Patent Information
- Application Number
- CN202510112042.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing ceramic composite separators have hole blockages at high temperatures, resulting in increased breathability and increased impedance, affecting the battery's charge and discharge rate performance. At the same time, their heat resistance is difficult to meet the high requirements of the market.
By providing a ceramic coating on the base film of the ceramic composite separator, the coating composition includes ceramic powder, polyacrylate adhesive, polyvinyl alcohol and sodium carboxymethylcellulose, and the characteristic parameters P of polyvinyl alcohol and sodium carboxymethylcellulose are controlled in the range of 0.02 to 0.36 to improve the heat resistance and breathability of the ceramic composite separator.
The low heat shrinkage and low breathability increment of ceramic composite separators are achieved, which improves the circulation performance and safety of the battery, and can better meet the high market requirements for heat resistance and safety.
Smart Images

Figure BDA0005256980120000171 
Figure BDA0005256980120000181
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a ceramic composite diaphragm and a battery. Background Art
[0002] As the commercial lithium-ion battery market expands, the requirements for safety and performance are constantly increasing. Compared with simple stretched polyolefin microporous membranes, ceramic composite diaphragms coated with ceramic coatings have better thermal stability, so that at high temperatures, ceramic composite diaphragms can still play a good role in physically isolating positive and negative electrodes to prevent contact short circuits.
[0003] Although the ceramic composite diaphragms in the prior art have a certain degree of heat resistance, they still generally have relatively serious pore blocking, which is manifested in that the air permeability of the ceramic composite diaphragm becomes higher and the impedance increases after coating, which in turn affects the charge and discharge rate performance of the battery; and with the continuous development of the industry, the market has higher and higher requirements for battery safety, and the heat resistance requirements of the diaphragm are also getting higher and higher, while the heat resistance of existing ceramic composite diaphragms is increasingly difficult to meet market requirements.
[0004] Therefore, there is an urgent need to develop a ceramic composite diaphragm that has both high heat resistance and low air permeability increment. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a ceramic composite diaphragm and a battery. The ceramic composite diaphragm has both low thermal shrinkage and low air permeability increment.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a ceramic composite diaphragm, the ceramic composite diaphragm comprising a base film and a ceramic coating disposed on at least one side of the base film, the ceramic coating comprising the following components: ceramic powder, polyacrylate adhesive, polyvinyl alcohol and sodium carboxymethyl cellulose;
[0008] The polyvinyl alcohol and sodium carboxymethyl cellulose satisfy the characteristic parameter P calculated according to the following formula of 0.02 to 0.36 (e.g., 0.02, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.36 or a range consisting of any two of them),
[0009] P = A / (B × C);
[0010] Wherein A is the degree of polymerization of polyvinyl alcohol, B is the ratio of the mass of polyvinyl alcohol to the mass of sodium carboxymethyl cellulose, and C is the weight average molecular weight of sodium carboxymethyl cellulose.
[0011] In the present invention, a ceramic composite diaphragm with good heat resistance and air permeability is prepared by adding polyvinyl alcohol and sodium carboxymethyl cellulose. By controlling the degree of polymerization of polyvinyl alcohol, the ratio of the mass of polyvinyl alcohol to the mass of sodium carboxymethyl cellulose and the weight average molecular weight of sodium carboxymethyl cellulose, the characteristic parameter P is within a specific range, and the role of polyvinyl alcohol and sodium carboxymethyl cellulose in improving the heat resistance and air permeability of the ceramic composite diaphragm can be better exerted. The prepared ceramic composite diaphragm has good thermal shrinkage and low air permeability increment.
[0012] In a second aspect, the present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet and the ceramic composite diaphragm described in the first aspect.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] The ceramic composite diaphragm of the present invention comprises a base membrane and a ceramic coating arranged on at least one side of the base membrane. Ceramic powder, polyacrylate adhesive, polyvinyl alcohol and sodium carboxymethyl cellulose are compounded in the ceramic coating. By controlling the characteristic parameters P of polyvinyl alcohol and sodium carboxymethyl cellulose within a specific range, the ceramic composite diaphragm has the characteristics of low thermal shrinkage and low air permeability increment. DETAILED DESCRIPTION
[0015] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0016] An embodiment of the present invention provides a ceramic composite diaphragm, which includes a base membrane and a ceramic coating arranged on at least one side of the base membrane, wherein the ceramic coating includes the following components: ceramic powder, polyacrylate adhesive, polyvinyl alcohol and sodium carboxymethyl cellulose.
[0017] The polyvinyl alcohol and sodium carboxymethyl cellulose satisfy the characteristic parameter P calculated according to the following formula of 0.02 to 0.36, for example, 0.02, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.36 or the range of any two thereof.
[0018] P = A / (B x C).
[0019] Wherein A is the degree of polymerization of polyvinyl alcohol, B is the ratio of the mass of polyvinyl alcohol to the mass of sodium carboxymethyl cellulose, and C is the weight average molecular weight of sodium carboxymethyl cellulose.
[0020] When P is lower than the lower limit, polyvinyl alcohol and sodium carboxymethyl cellulose cannot cooperate well with the ceramic powder in the ceramic coating to improve thermal shrinkage. When the P value is higher than the upper limit, the permeability increment of the ceramic coating increases significantly. Therefore, by controlling the characteristic parameter P of polyvinyl alcohol and sodium carboxymethyl cellulose within a specific range, the ceramic composite diaphragm can have both good thermal shrinkage and permeability increment.
[0021] For those skilled in the art, the values of A, B, and C can be freely selected to meet the range of the characteristic parameter P without departing from the spirit of the present invention.
[0022] In the present invention, at least one side of the base membrane refers to at least one of the two sides of the base membrane with the largest surface area and arranged opposite to each other. In the present invention, a ceramic coating can be arranged on one side of the base membrane to form a ceramic composite diaphragm, and a ceramic coating can also be arranged on both sides of the base membrane to form a ceramic composite diaphragm.
[0023] Exemplarily, the mass ratio of the polyvinyl alcohol to the mass of sodium carboxymethyl cellulose is 0.05 to 0.4, such as 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4 or a range consisting of any two thereof. The mass ratio of polyvinyl alcohol to sodium carboxymethyl cellulose of 0.05 to 0.4 is beneficial to further reduce the thermal shrinkage and air permeability increment of the ceramic composite diaphragm.
[0024] Exemplarily, the degree of polymerization of the polyvinyl alcohol is 1600 to 1800, such as 1600, 1620, 1640, 1660, 1680, 1700, 1720, 1740, 1760, 1780, 1800 or any two thereof. The degree of polymerization of the polyvinyl alcohol satisfies the above range, which is conducive to further improving heat resistance and air permeability and improving battery cycle performance.
[0025] Exemplarily, the weight average molecular weight of the sodium carboxymethyl cellulose is 100,000 to 200,000, such as 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, 160,000, 170,000, 180,000, 190,000, 200,000, or any two thereof. The weight average molecular weight of the sodium carboxymethyl cellulose satisfies the above range, which is beneficial to further improve the heat resistance and air permeability of the ceramic composite diaphragm, and is also beneficial to improve the anti-stripping performance of the ceramic coating and enhance the electrochemical safety.
[0026] Exemplarily, with the total mass of the ceramic coating as 100%, the mass proportion of the ceramic powder is 91% to 96%, such as 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96% or any two thereof. The mass proportion of the ceramic powder satisfies the above range, which is conducive to the formation of a good pore size and porosity of the ceramic coating while further improving the heat resistance and improving the electrochemical performance.
[0027] Exemplarily, the mass of the polyacrylate adhesive is 3% to 8% of the mass of the ceramic powder, such as 3%, 3.3%, 3.6%, 3.9%, 4.2%, 4.5%, 4.8%, 5.1%, 5.4%, 5.7%, 6%, 6.3%, 6.6%, 6.9%, 7.2%, 7.5%, 7.8%, 8% or any two thereof. The mass of the polyacrylate adhesive meets the above range, which is conducive to further improving the anti-stripping performance and heat resistance of the ceramic coating and ensuring electrochemical safety.
[0028] Exemplarily, based on the total mass of the ceramic coating as 100%, the total mass proportion of polyvinyl alcohol and sodium carboxymethyl cellulose is 0.4% to 2%, such as 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2% or any two thereof. When the total mass proportion of polyvinyl alcohol and sodium carboxymethyl cellulose meets the above range, it is beneficial to cooperate with other components in the coating to further jointly improve the heat resistance and air permeability of the ceramic coating.
[0029] There is no particular limitation on the mass proportion of polyvinyl alcohol and sodium carboxymethyl cellulose. It is understood that as long as the total mass proportion of polyvinyl alcohol and sodium carboxymethyl cellulose meets the above range and the total mass of the ceramic coating is 100%, the mass proportion of polyvinyl alcohol and sodium carboxymethyl cellulose is not 0%.
[0030] The ceramic powder in the ceramic coating is not particularly limited as long as it is electrochemically stable. That is, the ceramic powder does not undergo oxidation and / or reduction within the operating voltage range applied to the electrochemical device (e.g., 0 to 5 V for Li / Li+), and the ceramic powder can be used without special restrictions in the present invention. From the perspective of helping to improve the ionic conductivity of the electrolyte, preferably, the ceramic powder includes any one of aluminum oxide, boehmite, silicon oxide, magnesium oxide, barium sulfate or barium titanate, or a combination of at least two thereof.
[0031] The present invention has no particular limitation on the shape of the ceramic powder, which may be any existing ceramic powder shape, for example, any one or a combination of at least two of spherical, elliptical, quasi-spherical, plate-like or flake-like shapes.
[0032] The present invention does not particularly limit the particle size of the ceramic powder. The average particle size of the ceramic powder may preferably be 0.5 to 1.5 μm to ensure uniform thickness coating, appropriate porosity and good mechanical properties, and improve electrochemical safety, such as 0.5 μm, 0.6 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.5 μm or any two of them. The average particle size of the ceramic powder can be determined by conventional techniques known in the art. For example, a laser scattering particle size analyzer (Topsizer type particle size analyzer) can be used to characterize the average particle size of the ceramic powder, specifically including dispersing the ceramic particles in pure water, obtaining the D50 of the ceramic powder as the average particle size of the ceramic powder, and the D50 of the ceramic powder refers to the particle size corresponding to the cumulative particle size distribution percentage reaching 50%, which is the D50 of the ceramic powder; the composite ceramic coating can also be scanned by a scanning electron microscope (SEM), and the average particle size of the ceramic powder can be obtained by statistically analyzing and calculating the scanning results (such as Image J software analysis and calculation).
[0033] Illustratively, the acrylate adhesive includes a homopolymer of acrylate and / or a copolymer of acrylate.
[0034] Preferably, the homopolymer of acrylic acid ester includes a homopolymer formed by polymerization of any one of hydroxyethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, octyl methacrylate, n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate or styrene acrylate.
[0035] Preferably, the copolymer of acrylic acid ester includes a copolymer of at least two or more monomers selected from hydroxyethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, octyl methacrylate, n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate or styrene acrylate.
[0036] In other words, the acrylic adhesive can be selected from polymers formed by homopolymerization of the above-listed monomers, or polymers formed by copolymerization of two or more of the listed monomers, or a mixture of at least two or more of the homopolymers or copolymers formed by these monomers.
[0037] In the ceramic composite diaphragm of the present invention, the ceramic coating may also include additives such as dispersants, wetting agents, and pH adjusters, as non-limiting examples. In the ceramic slurry used to form the ceramic coating, a dispersant is added for the purpose of improving dispersibility, coating properties, or storage stability. In the ceramic slurry used to form the ceramic coating, a wetting agent is added, for example, for the purpose of improving affinity with a porous substrate. In the ceramic slurry used to form the ceramic coating, a pH adjuster is added, for example, for the purpose of adjusting pH.
[0038] The present invention does not particularly limit the dispersant. For example, the dispersant can be selected from any one of sodium polyacrylate, ammonium polyacrylate, carboxylates, hexametaphosphates or sulfonates, or a combination of at least two thereof.
[0039] The present invention does not particularly limit the wetting agent. For example, the wetting agent can be selected from any one of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether or polyether-modified polysiloxane, or a combination of at least two thereof.
[0040] The present invention does not particularly limit the pH adjuster. For example, the pH adjuster may be at least one of hydrochloric acid, phosphoric acid, sodium citrate, potassium citrate, sodium hydroxide, calcium hydroxide, potassium hydroxide, sodium bicarbonate or sodium carbonate.
[0041] The present invention does not impose any particular limitation on the mass percentage of additives such as dispersants, wetting agents, and pH adjusters, and the added content can be freely selected according to the purpose.
[0042] Exemplarily, based on the total mass of the ceramic coating as 100%, the mass proportion of the dispersant is 0.5% to 3.0%, for example, it can be 0.5%, 0.8%, 1.1%, 1.4%, 1.7%, 2.0%, 2.3%, 2.7%, 3.0% or any two thereof.
[0043] Exemplarily, based on the total mass of the ceramic coating as 100%, the mass proportion of the wetting agent is 0.5% to 1.5%, for example, it can be 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.5% or a range consisting of any two of them.
[0044] Exemplarily, based on the total mass of the ceramic coating as 100%, the mass proportion of the pH adjuster is 0.5% to 1.5%, for example, it can be 0.5%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.5% or a range consisting of any two of them.
[0045] Furthermore, in the separator of the present invention, if the porous substrate having a plurality of pores is a conventional porous substrate used for electrochemical devices, it is not limited to a specific kind of porous substrate. Exemplarily, the base film includes a polyolefin microporous membrane.
[0046] The polyolefin microporous membrane can be selected from, for example, polyethylene microporous membrane, polypropylene microporous membrane, polybutylene microporous membrane, polymethylpentene microporous membrane or a multilayer (two or more layers) composite membrane formed by any two or more thereof in any stacking order.
[0047] The present invention does not particularly limit the thickness of the polyolefin microporous membrane. Based on the viewpoints of mechanical strength and internal resistance, it preferably has a thickness between 1 μm and 5000 μm. More preferably, the thickness of the base membrane is 5 to 20 μm, for example, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm, 20 μm or a range consisting of any two of them.
[0048] The present invention does not particularly limit the average pore size and porosity of the polyolefin microporous membrane, but based on the viewpoints of mechanical strength, ion permeability and electrochemical safety, it is preferably a porosity between 30% and 65%, for example, it can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or any two of them; the average pore size is preferably in the range of 20nm to 100nm, for example, it can be 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm or any two of them. In addition, the pore structure of the polyolefin microporous membrane is formed by the staggered connection of a number of fibrils, which are formed by the polymer being stretched and oriented during the preparation process, and the preparation method of the polyolefin microporous membrane is not particularly limited.
[0049] Hereinafter, a preferred preparation method for manufacturing the ceramic composite diaphragm of the present invention is described below. However, the present invention is not limited thereto.
[0050] Exemplarily, the method for preparing the ceramic composite diaphragm comprises the following steps:
[0051] (1) Ceramic powder, polyacrylate adhesive, polyvinyl alcohol and sodium carboxymethyl cellulose are mixed to obtain ceramic slurry.
[0052] (2) coating the ceramic slurry obtained in step (1) on at least one surface of the base membrane and drying the slurry to obtain the ceramic composite diaphragm.
[0053] Preferably, the solvent includes at least one of deionized water, N-N dimethylformamide (DMF), N-N methylpyrrolidone (NMP), N-N dimethylacetamide (DMAC) or tetrahydrofuran (THF).
[0054] Based on the considerations of ceramic slurry stability and coating uniformity, preferably, the solid content of the ceramic slurry is 25% to 45%, for example, 25%, 30%, 35%, 40%, 45% or any two thereof.
[0055] Preferably, before step (2), the method may further include filtering the obtained ceramic slurry.
[0056] Exemplarily, the filter mesh number used for filtration is 200-400 mesh, so as to remove particles with excessively large particle size and metal foreign matter in the slurry to improve coating uniformity and safety of use. The filter mesh number can be, for example, 200 mesh, 220 mesh, 240 mesh, 260 mesh, 280 mesh, 300 mesh, 320 mesh, 340 mesh, 360 mesh, 380 mesh, 400 mesh or a range consisting of any two of them.
[0057] In addition, the ceramic slurry prepared in step (1) may be coated on at least one side of the surface of the base film using conventional coating methods known in the art, such as dip coating, die coating, roller coating or a combination thereof.
[0058] The present invention also provides a battery, comprising a positive electrode sheet, a negative electrode sheet and at least one of the ceramic composite diaphragms described above.
[0059] The ceramic composite diaphragm of the present invention can be used as a diaphragm between the positive electrode sheet and the negative electrode sheet.
[0060] The battery provided by the present invention is any device that can undergo electrochemical reactions, for example, it can include all kinds of primary batteries, secondary batteries, fuel cells, solar cells, capacitors (such as supercapacitors), etc. Specifically, lithium secondary batteries can be preferably used in secondary batteries, including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries or lithium ion polymer secondary batteries, etc.
[0061] Specifically, the battery may be a lithium secondary battery.
[0062] Specifically, the battery includes a positive electrode sheet, a negative electrode sheet and the above-mentioned ceramic composite diaphragm. The ceramic composite diaphragm is spaced between the positive electrode sheet and the negative electrode sheet to prevent the positive electrode sheet and the negative electrode sheet from contacting and short-circuiting. At the same time, during the charge and discharge process of the battery, the ceramic composite diaphragm allows active lithium ions to pass through. The active lithium ions pass through the diaphragm and migrate back and forth between the positive and negative electrodes to be deintercalated in the positive and negative electrodes to realize the charge and discharge process of the battery.
[0063] As mentioned above, the surface of the base film of the above-mentioned ceramic composite diaphragm is provided with a lithium replenishing layer, which can effectively release active lithium ions during the charge and discharge process of the battery. The released active lithium ions participate in the charge and discharge process of the battery, thereby replenishing the battery with lithium and compensating for the irreversible lithium loss generated during the charge and discharge process of the battery, thereby improving the coulomb efficiency of the battery in the first week, reducing the internal resistance of the battery, and improving the cycle performance of the battery.
[0064] Generally, the positive electrode sheet includes a positive electrode collector and a positive electrode coating located on at least one side surface of the positive electrode collector. The positive electrode coating can be provided on one side surface of the positive electrode collector, or on both the front and back sides of the positive electrode collector.
[0065] Specifically, the positive electrode current collector may be a conventional positive electrode current collector in the art, for example, the positive electrode current collector may include aluminum foil, but is not limited thereto.
[0066] Specifically, the positive electrode coating layer may include a positive electrode active material layer including a positive electrode active material, a first conductive agent, and a first binder.
[0067] Among them, the positive electrode active material can be a conventional positive electrode active material in the art, for example, the positive electrode active material includes a lithium-containing active material, and the lithium-containing active material can include one or more of nickel-cobalt-manganese ternary material (NCM), lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel manganese oxide, lithium-rich manganese-based solid solution or lithium manganese oxide, etc.
[0068] The first conductive agent may be a conventional conductive material in the art. For example, the first conductive agent may include one or more of conductive carbon black (SuperP), acetylene black, graphene, Ketjen black or carbon fiber, but is not limited thereto.
[0069] Among them, the first binder can be a conventional bonding material in the art, for example, the first binder can include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone or polyurethane, but is not limited thereto.
[0070] Specifically, based on 100% of the total mass of the positive electrode active material layer, the mass fraction of the positive electrode active material may be 70% to 99%, the mass fraction of the first conductive agent may be 0.5% to 15%, and the mass fraction of the first binder may be 0.5% to 15%.
[0071] In addition, the negative electrode sheet includes a negative electrode collector and a negative electrode coating present on at least one side of the negative electrode collector. The negative electrode coating can be provided on one side of the negative electrode collector, or on both the positive and negative sides of the negative electrode collector.
[0072] Specifically, the negative electrode current collector may be a conventional negative electrode current collector in the art, for example, the negative electrode current collector may include copper foil, but is not limited thereto.
[0073] Specifically, the negative electrode coating layer may include a negative electrode active material layer including a negative electrode active material, a second conductive agent, and a second binder.
[0074] The negative electrode active material may include graphite and / or silicon-based materials, and the silicon-based materials may include silicon-carbon and / or silicon-oxygen materials, but are not limited thereto.
[0075] The second conductive agent may be a conventional conductive material in the art. For example, the second conductive agent may include one or more of conductive carbon black (SuperP), acetylene black, Ketjen black, carbon fiber or graphene, but is not limited thereto.
[0076] Among them, the second binder can be a conventional bonding material in the art. For example, the second binder can include one or more of PVDF, carboxymethyl cellulose, styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, sodium polyacrylate, polyacrylonitrile copolymers or polyacrylic acid copolymers, but is not limited thereto.
[0077] Specifically, based on 100% of the total mass of the negative electrode active material layer, the mass fraction of the negative electrode active material may be 70% to 99%, the mass fraction of the second conductive agent may be 0.5% to 15%, and the mass fraction of the second binder may be 0.5% to 15%.
[0078] Exemplarily, the positive electrode sheet can be prepared by conventional methods in the art, such as by a coating method. For example, the preparation process of the positive electrode sheet includes: dispersing the components for forming the positive electrode coating, such as the positive electrode active material, the first conductive agent, the first binder, etc., in a first solvent, wherein the first solvent includes, for example, N-methylpyrrolidone (NMP), to prepare a positive electrode slurry; applying the positive electrode material to the surface of the positive electrode collector, and after drying, rolling and other processes, forming a positive electrode coating on the surface of the positive electrode collector to obtain a positive electrode sheet.
[0079] Illustratively, the negative electrode sheet can be prepared by conventional methods in the art, such as by a coating method. For example, the preparation process of the negative electrode sheet includes: dispersing the components for forming the negative electrode coating, such as the negative electrode active material, the second conductive agent, the second binder, etc., in a second solvent, the second solvent includes, for example, water (specifically, deionized water can be used), to prepare a negative electrode slurry; applying the negative electrode material to the surface of the negative electrode collector, and after drying, rolling and other processes, forming a negative electrode coating on the surface of the negative electrode collector to obtain a negative electrode sheet.
[0080] Generally, a battery includes a cell and a package that packages the cell, and the cell includes the above-mentioned positive electrode sheet, separator and negative electrode sheet. The cell can be a wound cell, that is, the positive electrode sheet, separator and negative electrode sheet are stacked in sequence and then wound to form a wound cell (rolled core); or, the cell can also be a laminated cell, that is, the cell includes a plurality of stacked positive electrode sheets and a plurality of negative electrode sheets, which are staggered and separated by a separator.
[0081] In the embodiments of the present application, the package body may be a conventional packaging material in the art. For example, the package body may include a soft packaging material (ie, the battery may be a soft packaging battery). The soft packaging material may include, for example, an aluminum-plastic film, but is not limited thereto.
[0082] In addition, the battery also includes an electrolyte, which may be a conventional electrolyte in the art, specifically a non-aqueous electrolyte.
[0083] For example, the electrolyte may include an organic solvent, an electrolyte salt, and an additive.
[0084] The organic solvent may include one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC) or ethyl propyl carbonate (EPC).
[0085] Among them, the electrolyte salt may include a lithium salt, and the lithium salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(difluorosulfonyl)imide (LiFSI) or lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).
[0086] The additive may include one or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), succinonitrile (SN) or adiponitrile (ADN).
[0087] Illustratively, the battery can be manufactured according to conventional methods in the art. For example, after assembling the positive electrode sheet, the separator and the negative electrode sheet into a battery cell, the battery cell is packaged with a packaging body, and then the battery is manufactured after processes such as liquid injection and formation. These processes are all conventional operations in the battery preparation process in the art and are not particularly limited.
[0088] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0089] The technical solution provided by the present invention will be clearly and completely described below in conjunction with examples and comparative examples. Obviously, the specific implementation methods described are only part of the implementation methods of the present invention, rather than all the implementation methods.
[0090] The materials used in the present invention can be purchased from the market or prepared by conventional methods; unless otherwise specified, the materials used in the present invention are as follows:
[0091] Polyethylene porous membrane: prepared by Shenzhen Xingyuan Material Technology Co., Ltd., with a thickness of 9 μm and a porosity of 50%.
[0092] Example 1
[0093] This embodiment provides a ceramic composite diaphragm, which includes a base film and a ceramic coating disposed on both sides of the base film, wherein the base film is a polyethylene microporous film (thickness of 9 μm, porosity of 50%), and the thickness of the ceramic coatings on both sides is 1.5 μm;
[0094] The ceramic coating includes the following components in mass percentage: 93.48% of ceramic powder (alumina, with an average particle size of 0.8 μm), 4.01% of polyacrylate adhesive (brand name 8524A, manufactured by Guangzhou Rongdong), 0.11% of polyvinyl alcohol (degree of polymerization of 1700, degree of alcoholysis of 81%), 1.07% of dispersant (ammonium polyacrylate dispersant, brand name DP03, manufactured by Beijing Xidema), 0.53% of wetting agent (polyether modified polysiloxane, brand name YDP-2129, manufactured by Hunan Guangxin) and 0.80% of sodium carboxymethyl cellulose (weight average molecular weight of 150,000).
[0095] The ceramic composite diaphragm is prepared by the following method:
[0096] (1) Ceramic powder, sodium carboxymethyl cellulose, a dispersant and deionized water were stirred and uniformly mixed, and then polyacrylate adhesive, polyvinyl alcohol and a wetting agent were added and continued to be stirred and dispersed uniformly, and then filtered through a 300-mesh filter to obtain a ceramic slurry, wherein the solid content of the ceramic slurry was 36.55%.
[0097] (2) The ceramic slurry prepared in step (1) is coated on both sides of the polyethylene microporous membrane, and then dried in an oven at 70° C. to obtain the ceramic composite diaphragm.
[0098] Example 2
[0099] The present embodiment provides a ceramic composite diaphragm, which differs from the embodiment 1 only in that the ceramic coating comprises the following components by mass percentage: ceramic powder (barium sulfate, average particle size of 0.8 μm) 93.48%, polyacrylate adhesive (brand 8524A, manufacturer Guangzhou Rongdong) 4.01%, polyvinyl alcohol (polymerization degree of 1600, alcoholysis degree of 81%) 0.11%, dispersant (sodium hexametaphosphate) 1.07%, wetting agent (fatty alcohol polyoxyethylene ether, brand SY003, manufacturer Wuxi Baijia) 0.53% and sodium carboxymethyl cellulose (weight average molecular weight of 200,000) 0.80%.
[0100] Other conditions are the same as in Example 1.
[0101] Example 3
[0102] The present embodiment provides a ceramic composite diaphragm, which differs from the embodiment 1 only in that the ceramic coating comprises the following components by mass percentage: ceramic powder (boehmite, average particle size is 1.0 μm) 94.70%, polyacrylate adhesive (brand 8524A, manufacturer Guangzhou Rongdong) 2.89%, polyvinyl alcohol (polymerization degree is 1800, alcoholysis degree is 81%) 0.13%, dispersant (ammonium polyacrylate, brand DP03, manufacturer Beijing Xidema) 0.50%, wetting agent (alkylphenol polyoxyethylene ether, brand NP-10, manufacturer Jinan Shunwang) 0.98% and sodium carboxymethyl cellulose (weight average molecular weight is 100,000) 0.80%.
[0103] Other conditions are the same as in Example 1.
[0104] Example 4
[0105] This embodiment provides a ceramic composite diaphragm, which differs from Embodiment 1 only in that sodium carboxymethyl cellulose (weight average molecular weight is 150,000) is replaced with sodium carboxymethyl cellulose (weight average molecular weight is 60,000) of the same mass, and other conditions are the same as those of Embodiment 1.
[0106] Example 5
[0107] This embodiment provides a ceramic composite diaphragm, which differs from Embodiment 1 only in that sodium carboxymethyl cellulose (weight average molecular weight is 150,000) is replaced with sodium carboxymethyl cellulose (weight average molecular weight is 250,000) of the same mass, and other conditions are the same as those of Embodiment 1.
[0108] Example 6
[0109] This embodiment provides a ceramic composite diaphragm, which differs from Embodiment 1 only in that polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 81%) is replaced with polyvinyl alcohol of the same mass (degree of polymerization: 1200, degree of alcoholysis: 81%), and other conditions are the same as Embodiment 1.
[0110] Example 7
[0111] This embodiment provides a ceramic composite diaphragm, which differs from Embodiment 1 only in that polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 81%) is replaced with polyvinyl alcohol of the same mass (degree of polymerization: 2200, degree of alcoholysis: 81%), and other conditions are the same as Embodiment 1.
[0112] Example 8
[0113] The present embodiment provides a ceramic composite diaphragm, which differs from Embodiment 1 only in that the mass percentage of polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 81%) is adjusted to 0.31%, and the mass percentage of sodium carboxymethyl cellulose (weight average molecular weight: 150,000) is adjusted to 0.60%, so that the ratio of the mass of polyvinyl alcohol to the mass of sodium carboxymethyl cellulose is 0.52, and other conditions are the same as those in Embodiment 1.
[0114] Example 9
[0115] The present embodiment provides a ceramic composite diaphragm, which differs from Embodiment 1 only in that the mass percentage of polyvinyl alcohol (polymerization degree of 1700, alcoholysis degree of 81%) is adjusted to 0.04%, and the mass percentage of sodium carboxymethyl cellulose (weight average molecular weight of 150,000) is adjusted to 0.87%, so that the ratio of the mass of polyvinyl alcohol to the mass of sodium carboxymethyl cellulose is 0.05, and other conditions are the same as those in Embodiment 1.
[0116] Example 10
[0117] The present embodiment provides a ceramic composite diaphragm, which differs from Embodiment 1 only in that the mass percentage of polyvinyl alcohol (polymerization degree of 1700, alcoholysis degree of 81%) is adjusted to 0.26%, and the mass percentage of sodium carboxymethyl cellulose (weight average molecular weight of 150,000) is adjusted to 0.65%, so that the ratio of the mass of polyvinyl alcohol to the mass of sodium carboxymethyl cellulose is 0.40, and other conditions are the same as those in Embodiment 1.
[0118] Comparative Example 1
[0119] This comparative example provides a ceramic composite diaphragm, which differs from Example 1 only in that the mass percentage of polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 81%) is adjusted to 0.41%, and the mass percentage of sodium carboxymethyl cellulose (weight average molecular weight: 150,000) is adjusted to 0.5%, and other conditions are the same as Example 1.
[0120] Comparative Example 2
[0121] This comparative example provides a ceramic composite diaphragm, which differs from Example 1 only in that the mass percentage of polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 81%) is adjusted to 0.02%, and the mass percentage of sodium carboxymethyl cellulose (weight average molecular weight: 150,000) is adjusted to 0.89%, and other conditions are the same as Example 1.
[0122] Comparative Example 3
[0123] This comparative example provides a ceramic composite diaphragm, which differs from Example 1 only in that polyvinyl alcohol is not added, the mass percentage of sodium carboxymethyl cellulose (weight average molecular weight of 150,000) is adjusted to 0.91%, and other conditions are the same as those of Example 1.
[0124] Comparative Example 4
[0125] This comparative example provides a ceramic composite diaphragm, which differs from Example 1 only in that sodium carboxymethyl cellulose is not added, the mass percentage of polyvinyl alcohol (degree of polymerization is 1700, degree of alcoholysis is 81%) is adjusted to 0.91%, and other conditions are the same as Example 1.
[0126] Comparative Example 5
[0127] This comparative example provides a ceramic composite diaphragm, which differs from Example 1 only in that sodium carboxymethyl cellulose (weight average molecular weight is 150,000) is replaced with sodium hydroxymethyl cellulose (weight average molecular weight is 150,000) of the same mass, and other conditions are the same as those of Example 1.
[0128] The following performance tests were performed on the ceramic composite diaphragms provided in the above Examples 1 to 10 and Comparative Examples 1 to 5.
[0129] (1) Air permeability increment: The air permeability values of the base film and the ceramic composite diaphragm were tested using an Asahi integrated air permeability tester, and the air permeability increment of the ceramic composite diaphragm was calculated using the following formula (unit: sec / 100ml):
[0130] Air permeability increment = air permeability value of ceramic composite diaphragm - air permeability value of base membrane;
[0131] (2) Thermal shrinkage rate: The ceramic composite diaphragm was cut into 297 mm × 210 mm samples. A wire frame of 100 mm × 100 mm was then drawn in the middle. The sample was placed between 22 A4 papers, i.e., 11 A4 papers on the top and 11 on the bottom. The sample was then placed on a stainless steel grid in a 150°C constant temperature oven and baked for 1 h. After the baking, the sample was taken out and allowed to cool to room temperature (25°C). The side length of the wire frame was measured and the average value L was taken. Thermal shrinkage rate = (100-L) / 100 × 100%.
[0132] The test results are shown in Table 1 below:
[0133] Table 1
[0134]
[0135]
[0136] In Table 1, “ / ” means that the result was not obtained.
[0137] It can be seen from the contents of Table 1 that the air permeability increment of the ceramic composite diaphragms provided in Examples 1 to 10 is ≤15sec / 100ml, and the thermal shrinkage rate is ≤6%. Preferably, the air permeability increment of the ceramic composite diaphragms provided in Examples 1 to 3, 6, 7, and 10 is ≤13sec / 100ml, and the thermal shrinkage rate of the double-sided coated composite diaphragms is ≤4%.
[0138] By comparing Example 1 with Examples 4-5, it can be seen that the ceramic composite diaphragm prepared by controlling the weight average molecular weight of sodium carboxymethyl cellulose within a specific range has better air permeability increment, heat resistance and better performance.
[0139] By comparing Example 1 with Examples 6-7, it can be seen that the ceramic composite diaphragm prepared by controlling the degree of polymerization of polyvinyl alcohol within a specific range has better air permeability increment and heat resistance.
[0140] By comparing Example 1 with Example 8, it can be seen that the ceramic composite diaphragm prepared by controlling the ratio of the mass of polyvinyl alcohol to the mass of sodium carboxymethyl cellulose within a specific range has better performance.
[0141] Compared with Example 1, if the characteristic parameter P is too small (Comparative Example 1), the thermal shrinkage rate of the prepared ceramic composite diaphragm is too high and the heat resistance is poor.
[0142] Compared with Example 1, if the characteristic parameter P is too large (Comparative Example 2), the air permeability increment of the prepared ceramic composite diaphragm is too high and the air permeability is poor.
[0143] Compared with Example 1, if polyvinyl alcohol (Comparative Example 3) or sodium carboxymethyl cellulose (Comparative Example 4) is not added, the thermal shrinkage rate of the prepared ceramic composite diaphragm is too high. It can be seen that only by adding polyvinyl alcohol and sodium carboxymethyl cellulose at the same time can the effect of improving the heat resistance and air permeability of the ceramic composite diaphragm be achieved.
[0144] Compared with Example 1, if sodium carboxymethyl cellulose is replaced with sodium hydroxymethyl cellulose of the same mass (Comparative Example 5), the heat resistance and air permeability of the ceramic composite diaphragm are poor.
[0145] The applicant declares that the present invention illustrates a ceramic composite diaphragm and a battery of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A ceramic composite diaphragm, characterized in that: The ceramic composite diaphragm comprises a base film and a ceramic coating disposed on at least one side of the base film, wherein the ceramic coating comprises the following components: ceramic powder, polyacrylate adhesive, polyvinyl alcohol and sodium carboxymethyl cellulose; The polyvinyl alcohol and sodium carboxymethyl cellulose satisfy the characteristic parameter P calculated according to the following formula, which is 0.02 to 0.36: P = A / (B × C); Wherein A is the degree of polymerization of polyvinyl alcohol, B is the ratio of the mass of polyvinyl alcohol to the mass of sodium carboxymethyl cellulose, and C is the weight average molecular weight of sodium carboxymethyl cellulose.
2. The ceramic composite diaphragm according to claim 1, characterized in that: The ratio of the mass of the polyvinyl alcohol to the mass of the sodium carboxymethyl cellulose is 0.05 to 0.
4.
3. The ceramic composite diaphragm according to claim 1 or 2, characterized in that: The polymerization degree of the polyvinyl alcohol is 1600-1800.
4. The ceramic composite diaphragm according to any one of claims 1 to 3, characterized in that: The weight average molecular weight of the sodium carboxymethyl cellulose is 100,000 to 200,000.
5. The ceramic composite diaphragm according to any one of claims 1 to 4, characterized in that: Taking the total mass of the ceramic coating as 100%, the mass of the ceramic powder accounts for 91% to 96%; Preferably, the mass of the polyacrylate adhesive is 3% to 8% of the mass of the ceramic powder; Preferably, based on the total mass of the ceramic coating being 100%, the total mass of the polyvinyl alcohol and the sodium carboxymethyl cellulose accounts for 0.4% to 2%.
6. The ceramic composite diaphragm according to any one of claims 1 to 5, characterized in that: The ceramic powder includes any one of aluminum oxide, boehmite, silicon oxide, magnesium oxide, barium sulfate or barium titanate, or a combination of at least two thereof; Preferably, the average particle size of the ceramic powder is 0.5-1.5 μm.
7. The ceramic composite diaphragm according to any one of claims 1 to 6, characterized in that: The acrylic ester adhesive includes an acrylic ester homopolymer and / or an acrylic ester copolymer; Preferably, the homopolymer of acrylic acid ester comprises a homopolymer formed by polymerization of any one monomer selected from hydroxyethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, octyl methacrylate, n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate or styrene acrylate; Preferably, the copolymer of acrylic acid ester comprises a copolymer formed by copolymerization of at least two or more monomers selected from hydroxyethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, octyl methacrylate, n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate or styrene acrylate.
8. The ceramic composite diaphragm according to any one of claims 1 to 7, characterized in that: The base film includes a polyolefin microporous film.
9. The ceramic composite diaphragm according to any one of claims 1 to 8, characterized in that: The base film has a thickness of 5 to 20 μm.
10. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and the ceramic composite diaphragm according to any one of claims 1 to 9.
Citation Information
Patent Citations
Low-air permeability ceramic coating separator for lithium ion battery and preparation method of ceramic coating separator
CN108598341A
Lithium-sulfur battery diaphragm and preparation method thereof
CN110112349A
Non-aqueous electrolyte secondary battery
WO2014157416A1